Battling desertification with decision support software - Sibiry Traoré, Pierre C. (Technical Centre for Agricultural and Rural Cooperation, 2006)
Sibiry Traore explains how decision support tools and GIS are being used to develop new, targeted agricultural techniques for Africa's desert margins.